Surgical and oncological management of renal medullary carcinoma in a young patient: a case report - Courcier, Jean; De La Taille, Alexandre; Bertolo, Riccardo; Amparore, Daniele; Erdem, Selcuk; Kara, Onder; Marchioni, Michele; Pavan, Nicola; Roussel, Eduard; Mamodaly, Maria; Campi, Riccardo; Ingels, Alexandre (Frontiers in Oncology, 2023)
Renal medullary carcinoma (RMC) is a rare form of renal cell carcinoma that has a poor prognosis. It is known to be associated with sickle cell trait or disease, although the exact underlying mechanisms are still unclear. The diagnosis is made through immunochemical staining for SMARCB1 (INI1). In this report, we present a case of a 31-year-old male patient with sickle cell trait who was diagnosed with stage III right renal medullary carcinoma . Despite the poor prognosis, the patient had a remarkable overall survival of 37 months. Radiological assessment and follow-up were primarily performed using 18F-FDG PET/MRI. The patient underwent upfront cisplatin-based cytotoxic chemotherapy before surgical removal of the right kidney and retroperitoneal lymph node dissection. Identical adjuvant chemotherapy was administered post-surgery. Disease relapses were detected in retroperitoneal lymph nodes, which were managed with chemotherapy and surgical rechallenges. We also discuss the oncological and surgical management of RMC, which currently relies on perioperative cytotoxic chemotherapy strategies as there are no known alternative therapies that have shown superiority to date.